A forward operator and its adjoint for GPS slant total delays. Issue 5 (23rd May 2015) - Zus, Florian; Dick, Galina; Heise, Stefan; Wickert, Jens
Abstract In a recent study we developed a fast and accurate algorithm to compute Global Positioning System (GPS) Slant Total Delay (STDs) utilizing numerical weather model data. Having developed a forward operator we construct in this study the tangent linear (adjoint) operator by application of the chain rule of differential calculus in forward (reverse) mode. Armed with these operators we show in a simulation study the potential benefit of GPS STDs in inverse modeling. We conclude that the developed operators are tailored for three (four)‐dimensional variational data assimilation and/or travel time tomography.